Altered ATP-sensitive potassium channels may underscore obesity-triggered increase in blood pressure - Fan Li-hong; Tian Hong-yan; Ma Ai-qun; Hu Zhi; Huo Jian-hua; Cao Yong-xiao (Acta Pharmacologica Sinica; Vol 29, No 10 (October 2008): Acta Pharmacologica Sinica, 2016)
Aim: To determine whether ATP-sensitive potassium channels are altered in VSMC from arotas and mesenteric arteries of obese rat, and their association with obesity-triggered increase in blood pressure. Methods: Obesity was induced by 24 weeks of high-fat diet feeding in male Sprague-Dawley rats. Control rats were fed with standard laboratory rat chow. Blood pressure and body weight of these rats were measured every 4 weeks. At the end of 24 weeks, KATP channel-mediated relaxation responses in the aortas and mesenteric arteries, KATP channel current, and gene expression were examined, respectively. Results: Blood pressure and body weight were increased in rats fed with high-fat diet. KATP channel-mediated relaxation responses, currents, and KATP expression in VSMC of both aortas and mesenteric arteries were inhibited in these rats. Conclusion: Altered ATP-sensitive potassium channels in obese rats may underscore obesity-triggered increase in blood pressure.